The Right to be Forgotten and Internet Governance: Challenges and Opportunities - Christopher T. Bavitz (Latin American Law Review, 2019)
This paper offers thoughts on the evolving nature and scope of Internet governance in the context of the development of the right to be forgotten. It summarises traditional frameworks for: (a) defining and operationalizing principles of Internet governance; and (b) distinguishing the types of issues that raise transnational governance concerns from the types of issues that are commonly considered the domain of local laws and norms.